2003
DOI: 10.1103/physrevc.67.044003
|View full text |Cite
|
Sign up to set email alerts
|

Positive pion absorption on3Heusing modern trinucleon wave functions

Abstract: We study pion absorption on 3 He employing trinucleon wave functions calculated from modern realistic N N interactions (Paris, CD Bonn). Even though the use of the new wave functions leads to a significant improvement over older calculations with regard to both cross section and polarization data, there are hints that polarization data with quasifree kinematics cannot be described by just two-nucleon absorption mechanisms.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…As a result of a systematic study of, for example, both NN and pd induced reactions, a deeper insight into the importance of three-body forces should be gained. For example, a recent microscopic calculation using purely two-body input to calculate the reaction π +3 He → ppp, found that the data [289,290] call for three-body correlations [291], confirming earlier studies [292]. It should be stressed, however, that this field is still in its infancy and a large amount theoretical effort is urgently called for.…”
Section: Meson Production On Light Nucleisupporting
confidence: 68%
“…As a result of a systematic study of, for example, both NN and pd induced reactions, a deeper insight into the importance of three-body forces should be gained. For example, a recent microscopic calculation using purely two-body input to calculate the reaction π +3 He → ppp, found that the data [289,290] call for three-body correlations [291], confirming earlier studies [292]. It should be stressed, however, that this field is still in its infancy and a large amount theoretical effort is urgently called for.…”
Section: Meson Production On Light Nucleisupporting
confidence: 68%
“…1 in reactions with either large momentum transfer or where higher partial waves become relevant, the effect of the second term is expected to be much more pronounced. Indeed, this has been already seen in a recent application of the wave function parametrization to π absorption on 3 He [26].…”
Section: The π 3 He Scattering Lengthmentioning
confidence: 58%
“…E.g., a calculation of quasifree pion absorption on nucleon pairs in 3 He based on the presented parameterization has been reported in Ref. [26].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation